PENINGKATAN KESADARAN BERAGAM MELALUI KAJIAN SYARIAT DAN TAREKAT DISERTAI SOSIALISASI: PEMBERDAYAAN MASYARAKAT YAYASAN MUKTI JAYA DALAM MENGAMALKAN AJARAN ISLAM (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This community service activity aims to enhance religious awareness among the public through an integrative approach combining sharia (Islamic legal principles) and tariqa (Islamic spirituality). The program was conducted as an educational seminar involving 20 participants from the surrounding community of Yayasan Mu’thi Jaya Indonesia, Tambun Utara, Bekasi. The implementation involved three key stages: preparation, execution, and evaluation. The results indicated a significant improvement in participants’ understanding of sharia and tariqa in a holistic and contextual manner. The activity also fostered greater religious inclusivity and strengthened social religious networks. Furthermore, it sparked local initiatives to form independent study groups (halaqah). Seminar materials and documentation were compiled into an internal report and educational leaflet. This program is recommended to be extended into regular study sessions or spiritual workshops as a sustainable form of Islamic community empowerment. Keywords: sharia, tariqa, religious awareness, community empowerment, Islamic spirituality.